2005
DOI: 10.1016/j.virol.2005.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy in chickens, geese and ducks of an H5N1-inactivated vaccine developed by reverse genetics

Abstract: We generated a high-growth H5N1/PR8 virus by plasmid-based reverse genetics. The virulence associated multiple basic amino acids of the HA gene were removed, and the resulting virus is attenuated for chickens and chicken eggs. A formalin-inactivated oil-emulsion vaccine was prepared from this virus. When SPF chickens were inoculated with 0.3 ml of the vaccine, the hemagglutinin-inhibition (HI) antibody became detectable at 1 week post-vaccination (p.v.) and reached a peak of 10log2 at 6 weeks p.v. then slowly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(142 citation statements)
references
References 51 publications
3
136
2
1
Order By: Relevance
“…In one of these studies, vaccination of ducks with inactivated influenza vaccine induced lower antibody titers and required larger dosage in comparison with vaccination of chickens. A second boost, however, seemed to help the relatively high antibody titers to last, although the boost generated only slightly higher antibody titers (Tian et al, 2005). As our results and previous studies show, ducks may be more likely to be re-infected with H9N2 even at shorter intervals.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In one of these studies, vaccination of ducks with inactivated influenza vaccine induced lower antibody titers and required larger dosage in comparison with vaccination of chickens. A second boost, however, seemed to help the relatively high antibody titers to last, although the boost generated only slightly higher antibody titers (Tian et al, 2005). As our results and previous studies show, ducks may be more likely to be re-infected with H9N2 even at shorter intervals.…”
Section: Discussionsupporting
confidence: 58%
“…Evidence also suggested that lack of secondary immune responses appeared to be a general feature of duck antibody responses (Kida et al, 1980;Lundqvist et al, 2006). Several inactivated influenza vaccines are currently used for controlling avian influenza in the laboratory and field studies (Tian et al, 2005;Nomura et al, 2012;). In one of these studies, vaccination of ducks with inactivated influenza vaccine induced lower antibody titers and required larger dosage in comparison with vaccination of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Mass vaccination against HPAI in Egypt was adopted on the basis of the predicted efficacy of H5N1 vaccines in a number of avian species (36)(37)(38)(39)(40) and the recommendation of FAO/OIE to use vaccination as part of a control strategy for HPAI. Furthermore, field trials of oil emulsion-whole-virus H5 vaccines have shown promise in controlling H5N1 influenza outbreaks in Vietnam and the People's Republic of China (41)(42)(43).…”
Section: Vaccinementioning
confidence: 99%
“…Moreover the vaccine demonstrated high immunogenicity in domestic ducks and geese that is very important for counter-epizootic actions. Morbidity and mortality of the vaccinated chickens, ducks and geese was not observed at their challenge with the highly pathogenic strain A/goose/Guangdong/1/96 (H5N1) in dose 7.5 log EID 50 , though insignificant virus shedding into environment was reported (Tian et al, 2005, Qiau et al, 2006.…”
Section: Discussionmentioning
confidence: 99%